CGIAR Initiative on National Policies and Strategies: Annual Technical Report 2022 - CGIAR Initiative on National Policies and Strategies (CGIAR System Organization, 2023)
CGIAR Technical Reporting has been developed in alignment with the CGIAR Technical Reporting Arrangement. This Initiative report is a Type 1 report and constitutes part of the broader CGIAR Technical Report. Each CGIAR Initiative submits an annual Type 1 report, which provides assurance on Initiative-level progress towards End of Initiative outcomes.